(untitled) (AGROINNOVATSIYА, 2024)
Coordinated or precision farming is not only a qualitatively new farming system, but also a new agricultural production strategy that uses information technology, collects and extracts information from many different sources, and the agro-industrial complex ensures the adoption of acceptable decisions on enterprise management.